The Quest for “Authenticity”. Three performances of a Bach’s fugue compared - Tiago Morais Ribeiro de Sousa (Aisthesis, 2016)
This paper is meant as a contribution to the general issue of authenticity in musical performances, an issue often debated at a rarefied, speculative level, by introducing a comparison between three case studies consisting of the performative choices in three renown recordings of performances of Bach’s Fugue BWV 1000: two on the classical guitar (Andrés Segovia and Julian Bream) and one on the lute (Hopkinson Smith). This approach allows us to pursue in greater detail the tacit aesthetic and ontological underpinnings of such options. Finally, I use the conceptual apparatus gathered to argue that, generally 1) there are no good reasons to believe that a “historicist” approach, per se, will add aesthetic value to a performance and, in particular 2) it is perfectly adequate to use the modern classical guitar in performing Bach’s works.